Sita Conservatoir terhadap Hasil Pertanian dalam Praktek Peradilan - Ni Made Puspasutari Ujianti; Ida Bagus Wimba Pratama; Anak Agung Sagung Laksmi Dewi Dewi (Jurnal Interpretasi Hukum, 2020)
The development in judicial practice appears as the prevalence of seizure of confiscation (conservatoir beslag) of agricultural products which in fact have not been regulated in article 227 HIR (Herziene Inlandsch Reglement) / 261 RBg (Rechtsreglement voor de Buiten-gewesten), so the judge must track down a legal basis in order to the decision handed down is more objective and justifiable. Departing from these conditions, the true confiscation of agricultural products needs to be explored through a scientific way. Therefore, through this research the issues related to the conservatoir beslag and its development in judicial practice are brought up as the object of the study. In this regard, there are two issues raised: (1) What is the arrangement for the placement of conservatoir beslag on agricultural products? (2) What is the legal basis for the judge’s consideration in granting the conservatoir beslag on agricultural products? The two issues are featured using the juridical-normative method and the statute and conceptual approaches. The results show that as stipulated in the applicable law, implementing the confiscation on the agricultural products in judicial practices can be executed even though it is not regulated in the HIR / RBg, in that such a confiscation on agricultural irreplaceable in a confiscation without including the confiscation of the land. This is because it is so difficult to estimate whether these agricultural products will be able to meet the demands of the plaintiff (creditor) or not.